Metoda wyznaczania sygnałów ostrzegawczych w przedsiębiorstwie na podstawie pasm strategicznych - Siedlecki, Rafał (Method of Determining Warning Signals Based on Strategic Band, 2007)
The article presents a method of determining warning signals. The presented proposal of determing the enterprise cycle of life and the model of forecasting the financial difficulties have been tested on financial data of Prokom SA. To determine the trajectory of company development, including the phases of enterprise cycle of life, logistic and log-logistic functions have been selected, as they are not only useful in economy, but also turned out to be useful in case of enterprise. The choice of these functions, based on the logistic growth law, is the result of financial parameters observation and research. It turned out that the functions approximate the enterprise development curve well, though accurate assigning of the analytical form of function describing the enterprise cycle of life, likewise assigning the trend function is a difficult task, due to lack of the universal methods of determining it.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 348-357